(untitled) (Communications in Mathematical Research, 2021)
In this paper, we give sufficient conditions to analyze the practical stability in the pth mean of stochastic differential equations with discontinuous coefficients. The Lyapunov-like function plays an important role in analysis. Some numerical computations are carried out to illustrate the theoretical results.